1970
DOI: 10.3126/narj.v4i0.4868
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of <i>Ralstonia solanacearum</i> Strains of Potato Wilt Disease from Nepal and Thailand

Abstract: Characterization of strains of Ralstonia solanacearum, the causal agent of potato bacterial wilt disease from Nepal and Thailand was performed based on pathogenicity, biochemical/physiological and serological tests. Fifteen R. solanacearum strains isolated from wilt infected potato plants and tubers grown in Nepal were characterized as race 3, biovar II based on the pathogenicity on different host plants, hypersensitive reaction on tobacco leaf and utilization of some sugars. Results of pathogenicity test show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 4 publications
4
13
0
1
Order By: Relevance
“…Result showed that all the isolates were able to cause rapid death of local cell of tissue between veins of tobacco leaves. These results are in accordance with the findings reported by Dhital et al (2001) who observed that R. solanacearum was able to produce HR in tobacco leaves. These results clearly indicated that like other plant pathogenic bacteria, R. solanacearum isolates possess Hrp type III secretion system which is responsible for inducing HR on tobacco leaves.…”
Section: Pathogenicity and Hypersensitivite Reaction (Hr) Testsupporting
confidence: 83%
“…Result showed that all the isolates were able to cause rapid death of local cell of tissue between veins of tobacco leaves. These results are in accordance with the findings reported by Dhital et al (2001) who observed that R. solanacearum was able to produce HR in tobacco leaves. These results clearly indicated that like other plant pathogenic bacteria, R. solanacearum isolates possess Hrp type III secretion system which is responsible for inducing HR on tobacco leaves.…”
Section: Pathogenicity and Hypersensitivite Reaction (Hr) Testsupporting
confidence: 83%
“…The isolates were also characterized by the hypersensitive response (HR) test in tobacco and also by different biochemical tests. These results were supported by the findings of Dhital et al (2001) who observed that R. solanacearum was able to produce wilt symptoms in potato, HR in tobacco leaves and was found positive by a series of biochemical tests. Also, the Gram staining and KOH solubility test indicated that the isolates of R. solanacearum are gram negative.…”
Section: Sugar Fermentation Testsupporting
confidence: 80%
“…In a host range study, all isolates were high to moderate pathogenic on potato and tomato, whereas on the other Solanaceous hosts such as eggplant and pepper were moderate to low pathogenic. The obtained results were in agreement with earlier reports stating that, characteristic of race 3 of R. solanacearum had limited host range (Buddenhagen et al, 1962;He et al, 1983;French, 1986;Dhital et al, 2001;Ibrahim et al, 2005).…”
Section: ------------------------------------------------------------supporting
confidence: 83%
“…All plantlets were planted in sterilized pots (20 cm diameter) containing sterilized peat-moss/sand (v/v) and allowed to grow for 6-8 weeks or until they were 15-20 cm high. Roots of each host plants were wounded and dipped in bacterial suspension (10 8 CFU mLG 1 ) of each isolate alone for 20 min and three replicates were used (Dhital et al, 2001). Degree of wilt was calculated according to He et al (1983), as average of three plants at four weeks after inoculation and rating scales were as followed: H, High (disease index 4.1-5.0); M, Moderate (2.6-4.0) and L, Low (1.1-2.5).…”
Section: Introductionmentioning
confidence: 99%